The results of tectonomagnetic investigation and recent geodynamic processes in ukrainian antarctic station “Academic Vernadsky” region - V. Y. Maksymchuk; V. G. Bakhmutov (Ukrainian Antarctic Journal, 2008)
The results of long-term (1998–2005) tectonomagnetic investigations in the Western Antarctic near Ukrainian Antarctic Station «Academic Vernadsky» are presented. The dynamics of geomagnetic field anomalies have been analyzed in connection with geology and tectonics of the region. The nature of tectonomagnetic anomalies is accounted for by piezomagnetic effect. The influence of stretching tectonic forces in sublatitudinal direction is connected with recent tectonic evolution of the area. The data are confirmed the other methods.